Perancangan User Experience Aplikasi Usaha Toko Kelontong dengan menggunakan Metode Human-Centered Design (Studi Kasus: Toko Assri Denpasar Bali) - Putri Stephanie Lesilolo; Herman Tolle; Retno Indah Rokhmawati (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2022)
The rise of Covid-19 cases that occurred in Indonesia from 2019 harmed all existing sectors. This has resulted in micro-entrepreneurs having to accept the uncertainty of when their business will return to normal. Assri store which are included in micro, small and medium enterprises (MSMEs) are certainly required to be more optimal, both in terms of quality and service. The development of information technology that has existed until now is a factor in the emergence of innovative applications that can facilitate work and also people's daily activities. It was found that there were deficiencies in the current system, namely the Assri store using a standard cash register to support sales transactions and the Olsera POS system. However, the POS system does not support online delivery and customer satisfaction information management features. Apart from features, the easy-to-use interface also supports users to be comfortable using the application for a long time. From the existing problems, it is necessary to design the user experience for the Assri store application. This design uses the HCD method which focuses on what is needed by the user. After designing the solution design, usability evaluation was also carried out using the scenario task method and the SUS questionnaire to 6 evaluators. From the results of the buyer's evaluation, the usability evaluation value obtained is 83.86% and is included in category A (excellent).